Ten‐Day Quadruple Therapy Comprising Proton Pump Inhibitor, Bismuth, Tetracycline, and Levofloxacin is More Effective than Standard Levofloxacin Triple Therapy in the Second‐Line Treatment of Helicobacter pylori Infection: A Randomized Controlled Trial. (September 2017) - Hsu, Ping‐I; Tsai, Feng‐Woei; Kao, Sung‐Shuo; Hsu, Wen‐Hung; Cheng, Jin‐Shiung; Peng, Nan‐Jing; Tsai, Kuo‐Wang; Hu, Huang‐Ming; Wang, Yao‐Kuang; Chuah, Seng‐Kee; Chen, Angela; Wu, Deng‐Chyang
Abstract : Objectives: Proton pump inhibitor (PPI)–amoxicillin–fluoroquinolone triple therapy is recommended as a second‐line treatment of Helicobacter pylori infection in the Maastricht V/Florence Consensus Report. However, the eradication rate of this standard salvage treatment is suboptimal. The objective of this study is to compare the efficacy of esomeprazole–bismuth–tetracycline–levofloxacin therapy (TL quadruple therapy) and esomeprazole–amoxicillin–levofloxacin triple therapy (AL triple therapy) in rescue treatment for H. pylori infection. Methods: Consecutive H. pylori ‐infected subjects after failure of first‐line therapies were randomly allocated to receive either TL quadruple therapy (esomeprazole 40 mg b.d., bismuth 120 mg q.d.s., tetracycline 500 mg q.d.s., and levofloxacin 500 mg o.d.) or AL triple therapy (esomeprazole 40 mg b.d., amoxicillin 500 mg q.d.s., and levofloxacin 500 mg o.d.) for 10 days. H. pylori status was assessed 6 weeks after the end of treatment. Results: The study was stopped after an interim analysis. Of 50 patients in the TL quadruple therapy, 49 (98.0%) had successful eradication of H. pylori infection. Cure of H. pylori infection was achieved in 36 of 52 patients (69.2%) receiving AL triple therapy. Intention‐to‐treat analysis demonstrated that TL quadruple therapy achieved a markedly higher eradication rate than AL triple therapy (difference: 28.8%; 95% confidence interval: 15.7% to 41.9%; P <0.001). Per‐protocol analysis yielded a similar result (97.8% vs. 68.6%; P <0.001). The two treatment groups exhibited comparable frequencies of overall adverse events (22.0% vs. 11.5%) and drug compliance (90.0% vs. 98.1%). The subgroup analysis showed that TL quadruple therapy was superior to AL triple therapy in patients with failure of either standard triple therapy (100% vs. 75.0%; P =0.010) or non‐bismuth quadruple therapy (95.0% vs. 52.6%; P =0.003). Conclusions: Ten‐day PPI–bismuth–tetracycline–levofloxacin quadruple therapy is a good option for rescue treatment of H. pylori infection following failure of standard triple or non‐bismuth quadruple therapy.